Impressive penetration of gender habitus in Ayao Woniwon, traditional proverbs of Yapen people in Serui town Papua - Mawene, Aleda; Yektiningtyas, Wigati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
Penetration of gender habitus in Ayao Woniwon, Traditional expressions of the Yapen people is carried out through cultural objects. The penetration is impressive which gives suggestions to men and women so that they perceive differences in behavior not as a cultural construction, but as something natural and legitimate. This study used qualitative data. Data collected in the form of symbols of cultural objects that are reflected in the sentence Ayao Woniwon. It was collected by using the technique of observation and deep interview from Yapen people who live in Serui city and its surroundings. The holistic approach was adopted by combining cultural study (form and content model) and literary study (semiotic approach and feminist literary criticism). The researcher found that Ayao Woniwon was created (anonymous) to protect males' roles that were symbolized by Kavi (loincloth), Yawainye (torch), Ayume (sail), Umbaio (wooden fork), and Epane (Nibong floor) and position of females on private-domestic work that was symbolized by Keepo Anane (papeda chopstick), Tewami (fireplace), and Ingkuja (Noken). The impressive penetration of gender habitus into Ayao Woniwon through these symbols causes gender disposition systems not to be eroded by time but continues to be inherited in the Yapen community.